2009
DOI: 10.1007/s11695-009-9844-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Nonobese Type 2 Diabetic Patients: An Interventional Study with Duodenal–Jejunal Exclusion

Abstract: In conclusion, duodenal-jejunal exclusion was an effective treatment for nonobese T2DM subjects. GJB was superior to standard care in achieving better glycemic control along with reduction in insulin requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 25 publications
4
47
0
4
Order By: Relevance
“…While investigating the mechanisms of action for gastrointestinal diversion procedures using duodenojejunal bypass, it was suggested that the exclusion of the duodenum and proximal jejunum would change nutrient movement, thus preventing the stimulation of the inappropriate signal that would promote insulin resistance 13,25,26 . Rubino et al 25 reported that duodenal exclusion of nutrient movement is the critical component for this reduction and subsequent control of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While investigating the mechanisms of action for gastrointestinal diversion procedures using duodenojejunal bypass, it was suggested that the exclusion of the duodenum and proximal jejunum would change nutrient movement, thus preventing the stimulation of the inappropriate signal that would promote insulin resistance 13,25,26 . Rubino et al 25 reported that duodenal exclusion of nutrient movement is the critical component for this reduction and subsequent control of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Geloneze et al 26 compared the potential advantages of the duodenojejunal exclusion surgery. Thus, a group of patients was operated upon using this technique and was compared to another paired control group that received the standard medical treatment for T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The operation does more than just limit intake, but also removes most-or perhaps all-of the ghrelin-producing cells in the gastric mucosa. In addition, two new procedures-the duodenojejunal bypass stomach-sparing operation [26] and ileal transposition [27][28][29]-have been tested in attempts to induce remission of diabetes without weight loss in lean or only modestly overweight patients with T2DM. However, both are still in the early stages of human trials (see Perspectives below).…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Recent animal investigations using duodenojejunal bypass, a stomach-preserving experimental model of RYGB, have shown that diabetes control is not a mere collateral effect of the treatment of obesity, but directly results from exclusion of the duodenum and proximal jejunum from the flow of nutrients. A recent report has described lean T2DM patients who experienced marked improvement of their diabetes with duodenojejunal exclusion surgery that was independent of changes in BMI, fat distribution and body composition [26]. Such a surgical approach was superior to standard care in achieving better glycaemic control, along with reduction or even interruption in insulin requirements.…”
Section: Perspectivesmentioning
confidence: 99%
“…The absence of the alleged "anti-incretin" in circulation would enhance the action of incretins and thus improve DM2. [101][102][103][104][105] Several authors claim to have demonstrated that derivation of the digestive transit to exclude a short segment of the proximal small intestine alone provides an improvement in diabetes mellitus type 2, irrespective of the effects of restricted food intake, loss of body weight, possible malabsorption of foods or the arrival of a smaller amount of digested food in the distal small intestine. Based on their results, these authors advocate surgery with duodenal exclusion as a valid alternative for the treatment of diabetes mellitus type 2.…”
Section: Introductionmentioning
confidence: 99%